Makna dan Nilai Moral Ritual Adat Hela Keta Perkawinan Suku Oepikan Desa As Manulea Kecamatan Sasitamean Kabupaten Malaka - Dionesia Seravia Mea; Yustina Sako; Emeliana Tai; Agustinus Seran (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The Meaning and Message of Moral Values ​​in the Hela Keta Traditional Ritual According to the Marriage of the Oepikan Tribe, As Manulea Village, Sasitamean District, Malaka Regency". The problem in this study is how the meaning and message of moral values ​​in the hela keta traditional ritual according to the marriage of the Oepikan Tribe, As Manulea Village, Sasitamean District, Malaka Regency. The purpose of this study is adjusted to the research problem, namely to describe the initial story of the philosophy of the hela keta traditional ritual in the marriage ceremony at the Oepikan Tribe Marriage, As Manulea Village, Sasitamean District, Malaka Regency. The method used in this study is the Qualitative method. The data collection techniques used in this study are interviews and documentation. The data analysis techniques used are data collection, data reduction, data assessment, and data interpretation. The results of the study show that the hela keta traditional ritual began in ancient times, various tribes lived in the place now called the Oepikan Tribe Marriage, their livelihoods were farmers. As a result of the many tribes inhabiting the place, the stock of food supplies has also run low. As a result, war was inevitable, the aftermath of the war was lasit fekan (broken relationship), this also had a major impact on the marriage system at that time. Aware of this, the tribal leaders sat down and discussed to find a solution to this problem, and the hela keta traditional ritual was created. The meaning of the hela keta traditional ritual is as a cleansing or purification from the curses of ancestors who fought in ancient times, and also the moral value message that can be taken from the hela keta traditional ritual, namely that the hela keta traditional ritual can repair and also unite the two large families of the tribe that had been broken up due to war.